1985
DOI: 10.1243/pime_proc_1985_199_084_02
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of a Sealed Squeeze-Film Bearing in a Flexible Support Structure

Abstract: In this paper attention is given to empirically modelling the hydrodynamics of a tightly sealed squeeze-film bearing in a flexible support structure simulating an aero-engine assembly, with a view to assessing its damping performance. It is found that predictable experimental results are obtained by employing an end-leakage factor which relates the outlet pressure around the bearing circumference to the corresponding ‘long-bearing’ pressure. The present work complements that covered in an earlier paper (1), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…In the literature there are many variants of the long and short bearing approximations [4,5]. The most prominent of these variants involves the combination of the short and long pressure solutions through an empirical "end-leakage factor"  that accounts for the degree of end-sealing [5,6]. This model is popular with industry and was used recently for whole-engine analysis with 5 SFDs using IRM and RHBM [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature there are many variants of the long and short bearing approximations [4,5]. The most prominent of these variants involves the combination of the short and long pressure solutions through an empirical "end-leakage factor"  that accounts for the degree of end-sealing [5,6]. This model is popular with industry and was used recently for whole-engine analysis with 5 SFDs using IRM and RHBM [7].…”
Section: Introductionmentioning
confidence: 99%
“…Since Cooper's investigation, the adoption of the SFD for turbo-machinery has increased, extending its application from the original field of aircraft turbine engines to industry. In most aero-engine applications, the purpose of squeeze-film damper is to introduce damping as a series element between the outer race of a rolling element bearing and its rather flexible housing, so that the rotor can safely negotiate any critical speeds and operate smoothly at higher speeds [3]. The vast investigations performed on SFDs have shown that damper force response is greatly influenced by conditions such as: oil feed mechanisms, end seals to restrict axial leakage, levels of inlet (supply) pressure and cavitation pressure of the lubricant, coupling of the damping device to the rotor system, and, in some circumstances, fluid inertia effects.…”
Section: Introductionmentioning
confidence: 99%
“…To take advantage of the innovations in the ®eld of parallel or vector processing, various attempts have been made to quasi-linearize the squeeze-®lm forces [6,7]. To take advantage of the innovations in the ®eld of parallel or vector processing, various attempts have been made to quasi-linearize the squeeze-®lm forces [6,7].…”
Section: Introductionmentioning
confidence: 99%